Effect of glycerol and Ca+² addition on physicochemical properties of edible carrageenan/porphyran based films obtained from Pyropia columbina red seaweed - Cian, Raúl Esteban (2014)
The aim of this work was to study the effect of glycerol and Ca+2 addition on physicochemical properties of phycocolloids (carrageenans/porphyrans) based films obtained from Pyropia columbina aqueous fraction. Films were formed by casting from aqueous dispersions of phycocolloids-enriched fraction (P) with different levels of glycerol (0, 12.5 and 25 g/100 g dry solid) and the optional addition of Ca+2 (16 g/100 g dry solid), yielding 6 formulations according to a multi-factorial design (P, PG1, PG2, PCa, PCaG1 and PCaG2). All films were homogeneous, flexible and slightly greenish. Moisture content, water solubility and water vapor permeability of films were significantly increased by adding glycerol to the formulation (11%, 12% and 6%, respectively). Increasing glycerol content in formulations (12.5 to 25 g/100 g dry solid), allow obtaining more stretchable but less resistant films (with less tensile strength and elastic modulus) than those produced without plasticizer (P). Ca+2 addition masked glycerol effect in some properties (water solubility and water vapor permeability), but in others, the effect of Ca+2 was added to the plasticizer glycerol effect (mechanical properties). Ca+2 could stabilize the three-dimensional structure of P phycocolloids by interactions between sulfate groups, promote water retention and open film structure. Use of these additives yielded films from Pyropia columbina with a wide range of mechanical properties, thus extending the scope of these materials